2005
DOI: 10.1103/physreva.72.052326
|View full text |Cite
|
Sign up to set email alerts
|

Standard forms of noisy quantum operations via depolarization

Abstract: We consider noisy, non-local unitary operations or interactions, i.e. the corresponding evolutions are described by completely positive maps or master equations of Lindblad form. We show that by random local operations the completely positive maps can be depolarized to a standard form with a reduced number of parameters describing the noise process in such a way that the noiseless (unitary) part of the evolution is not altered. A further reduction of the parameters, in many cases even to a single one (i.e. glo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 29 publications
0
86
0
Order By: Relevance
“…A related protocol, twirling a quantum channel with Haar-random unitary operators, has been studied recently for the purpose of reducing a generic gate to a standard form, which is among the results of Ref. [10], where it was also shown that the Clifford group is also an adequate substitute for that task. Moreover, the task of generating typical generic entanglement has been studied in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A related protocol, twirling a quantum channel with Haar-random unitary operators, has been studied recently for the purpose of reducing a generic gate to a standard form, which is among the results of Ref. [10], where it was also shown that the Clifford group is also an adequate substitute for that task. Moreover, the task of generating typical generic entanglement has been studied in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…with the symplectic inner product S P on the index space (see [19] for further details; these techniques are discussed also in [10]). Therefore, setting r k = α k β k leads to the above form.…”
Section: This Follows From Noting That We Can Expressmentioning
confidence: 99%
“…[22]) in such a way that the diagonal elements are not altered, p k = p k,k . This often allows one to restrict considerations to Pauli-diagonal channels, and makes such channels particularly important.…”
Section: Quantum Communication Via Noisy Channelsmentioning
confidence: 99%
“…Consider a quantum channel E and the associated bipartite mixed statê E = 1l ⊗ E|Φ Φ| (22) that is obtained by sending part of a maximally entangled state |Φ through the channel E. Consider also the channelÊ which is generated when using a state E for teleportation. Notice that for Pauli-diagonal channels E P (see Eq.…”
Section: Equivalence Between Qecc and One-way Eppmentioning
confidence: 99%
“…In standard purification protocols this is enforced by depolarizing the transmitted state. Instead, here we depolarize the channels E j to a Pauli-diagonal form [16]…”
Section: Blind Purificationmentioning
confidence: 99%